2019
DOI: 10.1111/psyp.13329
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory sinus arrhythmia reactivity across empirically based structural dimensions of psychopathology: A meta‐analysis

Abstract: Low resting respiratory sinus arrhythmia (RSA) is observed in many mental health conditions, including anxiety disorders, mood disorders, schizophrenia spectrum disorders, disruptive behavior disorders, and nonsuicidal self‐injury, among others. Findings for RSA reactivity are more mixed. We evaluate associations between RSA reactivity and empirically derived structural categories of psychopathology—including internalizing, externalizing, and thought problems—among physically healthy adults. We searched multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(122 citation statements)
references
References 72 publications
5
113
3
1
Order By: Relevance
“…Larger reductions in response to a worry induction predict development of emotional distress and sleep disturbance during periods of academic stress (Gouin, Deschenes, & Dugas, ; MacNeil et al, ). These findings support the view that larger reductions in vmHRV in response to emotionally evocative challenges are associated with a broad vulnerability factor (Beauchaine & Thayer, ), but this may vary across types of adjustment difficulties (Beauchaine et al, ).…”
Section: Empirical Findingssupporting
confidence: 80%
See 3 more Smart Citations
“…Larger reductions in response to a worry induction predict development of emotional distress and sleep disturbance during periods of academic stress (Gouin, Deschenes, & Dugas, ; MacNeil et al, ). These findings support the view that larger reductions in vmHRV in response to emotionally evocative challenges are associated with a broad vulnerability factor (Beauchaine & Thayer, ), but this may vary across types of adjustment difficulties (Beauchaine et al, ).…”
Section: Empirical Findingssupporting
confidence: 80%
“…A wide‐ranging and rapidly growing body of research on self‐regulation, emotion, and interpersonal processes examines parasympathetic nervous system activity, measured as heart rate variability (HRV). As described in recent reviews (Balzarotti, Biassoni, Colombo, & Ciceri, ; Beauchaine et al, ; Laborde, Mosley, & Thayer, ), HRV is broadly related to adaptive functioning, suggesting robust parasympathetic correlates of several adjustment processes. Further, because HRV also predicts physical health, this parasympathetic mechanism could contribute to the association of emotional adjustment, social functioning, and self‐regulation with subsequent health (Hillebrand et al, ; Thayer & Lane, ; Thayer, Yamamoto, & Brosschot, ; Williams, Koenig et al, 2019).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Fifteen (29%) of the children were reported to take medication, most commonly for attention problems/hyperactivity, asthma, allergies, or seizures. Anticholinergic medications and SSRIs may be related to psychophysiological measurement [Beauchaine et al, ; Green, Nuechterlein, & Satz, ]; only one child was reported to take the former, and no children were taking SSRIs at the time of the present study.…”
Section: Methodsmentioning
confidence: 88%